The evolution of knowledge navigator model: The construction and application of KNM 2.0. (15th June 2020) - Hsieh, Ping Jung; Lin, Chinho; Chang, Shofang
Highlights: Knowledge Navigator Model proposed in 2009 has been practically promoted in Taiwan. This study described the evolution of KNM to become KNM 2.0. KNM 2.0 covers the contemporary topics such as big data and KM performance. Qualitative and quantitative research methods were conducted to construct KNM 2.0. The results of a 139 cases survey revealed the applicability of KNM 2.0. Abstract: The knowledge management (KM) maturity model provides a framework against which both old and new KM initiatives can be assessed to determine whether they are capable of generating new knowledge. Knowledge Navigator Model (KNM) proposed in 2009 (Hsieh et al., 2009) has been promoted in Taiwan to assist organizations to evaluate their KM status, and also aided to be a diffusion platform for government, academic and practice to exchange their KM experience. However, for the past 10 years, the industrial environment has been constantly changing that has brought the developing of KM practice. This study described the evolution of KNM to become KNM 2.0 in terms of construction and application. Qualitative and quantitative research methods were conducted to construct the proposed three modules of KNM 2.0. A 139 cases survey was employed and the results reveal the applicability of KNM 2.0. Our research contributes to the body of concepts on KM maturity models that could evaluate the readiness of service-oriented knowledge economy, big data and smart factory, and strategic KM performance. The proposed KNM 2.0, with these features which are novel and rapidly expanding fields, has been developed as an online Knowledge Management Evaluation (KM evaluation) website available for the practice to use to better understand their overall value brought by contemporary KM. Moving forward, by using KNM 2.0 to continually collect the data from the industries in Taiwan, it is expected to obtain more information about the practical KM that keeps developing with the trends, and also keep playing the role to distribute the contemporary concepts of KM. The KM experience could be referenced and the methodology could be applied to other countries.